Evolving Toward Shared HIV Care Using the Champlain BASE eConsult Service - Kendall, Claire E. (MDM Policy Pract, 2019)
Background. Electronic consultation (eConsultation) is a potential strategy to improve access to specialist expertise and facilitate collaborative care models. The Champlain BASE eConsult service allows for asynchronous communication between primary care providers (PCP) and specialists on a secure, web-based system. HIV experts accessible include HIV physician specialists, HIV pharmacists, and social workers with expertise in HIV. Objective. This study aims to describe the use, value, and utility of this eConsultation service in the care of people living with HIV and to characterize the common question types and clinical topics asked by PCPs. Methods. We analyzed the data from eConsults sent to the HIV specialty group in Ontario’s Champlain Local Health Integration Network between February 2015 and December 2017. Usage data and close-out survey responses were analyzed using descriptive statistics, eConsults were classified using a predefined list of validated taxonomy, and a thematic analysis was performed on the consultation logs to identify common clinical themes. Results. Among the 46 eConsults, the most common question type related to drug treatment (58.7%, n = 27) and management (19.6%, n = 9). The main clinical themes involved the care of significant complexities in people living with HIV, such as comorbidities and drug interactions, and suggestions of coordinated patient care. As well, eConsult was used for advice regarding pre-exposure prophylaxis for HIV-negative patients at risk of HIV infection. PCPs highly valued the eConsult service (average rating 4.8/5). Conclusion. Overall, this study demonstrates that eConsult provides an efficient and valuable service to PCPs caring for patients living with or at risk for HIV by improving access to HIV specialists and facilitating the delivery of team-based comprehensive care.